Plants and microplastics: Growing impacts in the terrestrial environment - Wong, Amanda E.; Taylor, Gail (Frontiers in Plant Science, 2025)
Microplastic pollution is a largely unexplored yet pervasive environmental problem, in terrestrial environments, including impacts on plants and food crops. Plant growth and function are most often negatively impacted by plastic exposure, but these pollutants can also stimulate plant processes such as root growth and there is a tentative suggestion that monocotyledonous may be less sensitive to microplastics than dicotyledonous plants. Toxic effects include reduced plant biomass, chlorophyll content, photosynthesis, and changes to antioxidants, metabolites, and nutrients, with stimulatory effects often found at lower concentrations of exposure. There is strong evidence that roots can directly uptake and translocate plastic particles at 1 µm and under in size. Indirect effects include interactions of microplastics with other pollutants, soil properties, and soil organisms. These findings have potentially wide-ranging implications for terrestrial ecosystem function and human health. Future research should further elucidate the mechanisms of plant microplastic toxicity at realistic concentrations. This short review highlights the significance of microplastics in the terrestrial environment, where they can occur at higher concentrations than in the aquatic environment, with likely impacts on important food crop plants. The significance of these findings for human and ecosystem health remains to be elucidated and we make four recommendations to the scientific community for improved future experimentation.